2018
DOI: 10.1002/ejsp.2541
|View full text |Cite
|
Sign up to set email alerts
|

When goals loom darker: Goal ambivalence moderates the effect of goal proximity on goal‐related motivation

Abstract: This research extends previous work on the self‐regulation of goal striving as well as effects of temporal and psychological distance on motivation. Borrowing from classic work on goal gradients and approach‐avoidance conflicts, we predicted that the experience of ambivalence toward a personal goal moderates the extent to which feeling or being close to goal attainment affects motivation, such that greater proximity to the goal has a negative effect on motivation at higher levels of experienced goal ambivalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(190 reference statements)
0
2
0
Order By: Relevance
“…While the increase in action intentions via efficacy when the goal is close is consistent with research on the effects of personal goal proximity found in the motivation literature (Bandura & Schunk, 1981; Koo & Fishbach, 2012; Stern et al, 2013), the absence of a direct effect of goal proximity is not. For example, based on the goal gradient hypothesis which originated in animal behavior research (Hull, 1932), studies have found that unless the goal is negative or ambivalent (Brandstätter et al, 2019), people put more effort toward it as goal proximity increases (Kivetz et al, 2006; Mutter & Kundisch, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While the increase in action intentions via efficacy when the goal is close is consistent with research on the effects of personal goal proximity found in the motivation literature (Bandura & Schunk, 1981; Koo & Fishbach, 2012; Stern et al, 2013), the absence of a direct effect of goal proximity is not. For example, based on the goal gradient hypothesis which originated in animal behavior research (Hull, 1932), studies have found that unless the goal is negative or ambivalent (Brandstätter et al, 2019), people put more effort toward it as goal proximity increases (Kivetz et al, 2006; Mutter & Kundisch, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also examined the simultaneous activation of approach and avoidance motivations when they are directed at the same object (Ajzen & Kruglanski, 2019; Brown, 1948; Cavallo et al, 2012; Lewin, 1931; Lieberman, 1969; McCarty, 1967; N. E. Miller, 1944; Rigby, 1954; Robinson et al, 2016), which is inherent in the research on ambivalence (Brandstätter et al, 2018; Cacioppo & Berntson, 1994; Cacioppo et al, 1997; Jonas et al, 2000; Nikitin & Freund, 2009; Norris & Wu, 2021; Schneider et al, 2015; Wilson et al, 2000) and central to the research on self-control (Becker et al, 2015; Briki, 2018; Fishbach & Shah, 2006; Heatherton & Baumeister, 1996; Loewenstein, 1996; Metcalfe & Mischel, 1999; Muraven & Baumeister, 2000; Sklar & Fujita, 2020).…”
mentioning
confidence: 99%